(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация: в статье рассматриваются белки и аминокислоты как ключевые компоненты живых организмов. Описаны их природа, состав, структурные особенности и механизм образования пептидных связей. Подробно изложены уровни организации белковых молекул. Особое внимание уделено функциям белков в живых организмах. Показано биологическое значение белков как универсальных молекул, участвующих в жизненно важных процессах. Annotation: The article examines proteins and amino acids as key components of living organisms. Their nature, composition, structural features, and the mechanism of peptide bond formation are described. The levels of protein molecule organization. Special attention is given to the functions of proteins in living organisms. The biological significance of proteins as universal molecules involved in vital processes is highlighted.